2014
DOI: 10.1166/jnn.2014.8878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aspect Ratio and Temperature on Magnetic Properties of Permalloy Nanowires

Abstract: Arrays of permalloy nanowires (NWs) were fabricated into the pores of self-engineered Anodic Aluminium Oxide (AAO) templates by a simple electrodeposition technique (EDT) with a diameter -200 nm. By varying the length of the nanowires from 1.5 to 7.5 microm, got corresponding changes in aspect ratio from 7.5 to 37.5. We studied the growth and structural properties of permalloy nanowires using scanning electron microscopy, X-ray diffraction spectra and transmission electron microscopy. We performed the magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the ferromagnetic property of the deposited Py nanowire arrays is not significant, which may be due to the magnetostatic coupling effect between adjacent nanowires. [31,32] In addition, it is also observed that the change of the magnetic property along the axis direction is more obvious than along the radial direction under different electrochemical deposition conditions.…”
Section: Resultsmentioning
confidence: 97%
“…However, the ferromagnetic property of the deposited Py nanowire arrays is not significant, which may be due to the magnetostatic coupling effect between adjacent nanowires. [31,32] In addition, it is also observed that the change of the magnetic property along the axis direction is more obvious than along the radial direction under different electrochemical deposition conditions.…”
Section: Resultsmentioning
confidence: 97%
“…It is important to keep in mind that the physics of the problem lies mainly in the nucleation and propagation of DWs, whose width is related to the diameter of the nanowire, and it is independent of its length (as long as the DW width is smaller than the length of the wire and that we are considering an isolated nanowire). However, in the case of an interacting array of nanowires, the length of these plays a fundamental role on their coercivity [31]. If one assumes that all the wires are uniformly magnetized along their axis, then we can imagine that there will be magnetic charges on the cylinder caps.…”
Section: Resultsmentioning
confidence: 99%
“…Because MNs show novel and interesting properties with a specific structure, they have been studied to investigate the dependence of geometrical parameters such as the wire diameter [36][37][38], segment thicknesses [28,[37][38][39][40][41][42], and aspect ratio [43,44] on the magnetic properties. Moreover, the hysteresis properties of the Ising-type multisegment nanowire with alternating magnetic spin-1/2 and spin-1 segments were investigated by using the EFT with correlations.…”
Section: Introductionmentioning
confidence: 99%